PENGARUH KOMUNIKASI INTERPERSONAL DAN DISIPLIN TERHADAP PRODUKTIVITAS PENGAWAS DI DINAS PENDIDIKAN KABUPATEN BEKASI - Yuliana Yuliana (Jurnal Manajemen Pendidikan, 2013)
The objective of this research was to determine the direct effect of interpersonal communication and discipline on supervisor productivity. The study was conducted at Education Department Bekasi Regency. The research was conducted using survey method with qualitatif approach an path analysis technique. Based on the result of data analysis in this research it is concluded: (1)the interpersonal communication have positive direct effect to productivity, (2)the discipline have positif direct effect to productivity, (3)the interpersonal communicaton have positive direct effect to discipline. The supervisor productivity can be improved by improvement the interpersonal communication and discipline.